Metaphors of masculinity : sex and status in Andalusian folklore - Brandes, Stanley H. (Publications of the American Folklore Society. New series ;, 1980)
In the Andalusian communities throughout the olive-growing region of southeastern Spain men show themselves to be primarily concerned with two problems of identity: their place in the social hierarchy, and the maintenance of their masculinity in the context of their culture.In this study of projective behavior as found in the folklore of an Andalusian town, Stanley Brandes is careful to support psychological interpretations with ethnographic evidence. His emphasis on male folklore provides a timely complement to current research on women.